CHARACTERISTIC ORGANOLEPTIC, AND PROTEIN CONTENT OF COOKIES FROM MOCAF FLOUR WITH ADDITION LOMEK FISH FLOUR - Novia, Reni; Manurung, Jelita; Yolanda Fortuga, Nia; Panjaitan, Raini; Irwanto, Reno; Arisman, Yessy (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The problem of wasting still occurs quite frequently in Indonesia so efforts are needed to overcome this so that it does not cause detrimental impacts in both the short and long term. One effort that can be made is by providing food that is high in protein originating from local food ingredients such as mocaf flour and lomek fish flour. One product that can be developed from this material was cookies. Therefore, in this research, researchers will develop a cookies product from mocaf flour with the addition of lomek fish flour. The aim of this research was to determined the organoleptic characteristics and protein content of cookies products made from mocaf flour with the addition of lomek fish flour. The research design used was a Completely Randomized Design (CRD). In this research, cookies product manufacturing, organoleptic testing, determination of the selected formula, and analysis of protein content were carried out. The organoleptic test results showed that the color, taste and texture attributes showed significantly different results (p-value<0.005) while the aroma attributes showed results that were not significantly different (p-value>0.005). The organoleptic test results show that formula 2 was preferable compared to formulas 1 and 3, especially in terms of taste attributes. Based on this, formula 2 was selected as the selected formula. Formula 2 contains 21.0 grams of protein per 100 grams of product and can be claimed as a high-protein product. This product requires further research related to organoleptic testing for the target group, complete proximate and amino acid content, and product shelf life.